Advanced Lithium–Sulfur Batteries Enabled by a Bio‐Inspired Polysulfide Adsorptive Brush. (26th October 2016) - Zhao, Teng; Ye, Yusheng; Peng, Xiaoyu; Divitini, Giorgio; Kim, Hyun‐Kyung; Lao, Cheng‐Yen; Coxon, Paul R.; Xi, Kai; Liu, Yingjun; Ducati, Caterina; Chen, Renjie; Kumar, R. Vasant
Abstract : Issues with the dissolution and diffusion of polysulfides in liquid organic electrolytes hinder the advance of lithium–sulfur batteries for next‐generation energy storage. To trap and re‐utilize the polysulfides without hampering lithium ion conductivity, a bio‐inspired, brush‐like interlayer consisting of zinc oxide (ZnO) nanowires and interconnected conductive frameworks is proposed. The chemical effect of ZnO on capturing polysulfides has been conceptually confirmed, initially by using a commercially available macroporous nickel foam as a conductive backbone, which is then replaced by a free‐standing, ultra‐light micro/mesoporous carbon (C) nanofiber mat for practical application. Having a high sulfur loading of 3 mg cm −2, the sulfur/multi‐walled carbon nanotube composite cathode with a ZnO/C interlayer exhibits a reversible capacity of 776 mA h g −1 after 200 cycles at 1C with only 0.05% average capacity loss per cycle. A good cycle performance at a high rate can be mainly attributed to the strong chemical bonding between ZnO and polysulfides, fast electron transfer, and an optimized ion diffusion path arising from a well‐organized nanoarchitecture. These results herald a new approach to advanced lithium–sulfur batteries using brush‐like chemi‐functional interlayers. Abstract : A bio‐inspired polysulfide adsorptive brush, consisting of zinc oxide nanowires and conductive frameworks, has been designed and used as a chemi‐functional interlayer to advance lithium–sulfur batteries by effectively trapping and re‐utilizing migrating polysulfides. With the incorporation of this hierarchically nano‐structured interlayer, good cycle stability and rate capability have been achieved for a readily available sulfur/multi‐walled carbon nanotube composite cathode.